Analisis Strategi Manajemen Waktu Pada Remaja - Adilla, Ratu (Jurnal Bimbingan dan Konseling Pandohop, 2023)
The phenomenon of difficulty managing time often occurs during adolescence. In teenagers' lives, effective time management is very important because sociologically, teenagers are vulnerable to external influences. This is indicated by students who cannot determine the time to study, do not study regularly, do not have a study schedule, are slow in completing assignments, and do not submit assignments on time. Utilizing time management strategies can improve performance and free up more time for higher priority tasks. This research was conducted to find out appropriate strategies for time management in adolescents. This research uses the literature research method, which is carried out by searching for and collecting theoretical references, then analyzing them. Based on the findings and discussion, it can be concluded that time management components such as time assessment, goal setting, planning, prioritization, and monitoring also produce better results.